2006
DOI: 10.1007/s11661-006-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of crystallographic texture during equal channel angular extrusion of copper: The role of material variables

Abstract: The evolution of crystallographic texture during equal channel angular extrusion (ECAE) using route A has been investigated experimentally as well as by simulations for three types of materials: pure, commercially pure, and impure (cast) copper. The ECAE texture of copper can be compared with simple shear textures. However, there are deviations in terms of location of the respective components. These differences can be nearly reproduced using a recent flow line approach for ECAE deformation (L.S. Tóth, R. Arru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…These are typically referred to as α and β fibres, respectively, and have been observed following the deformation that occurs during rolling, which can be idealized as plane-strain compression. The deformation texture changes considerably in the highly strained region (III) in figure 8d, where the texture is similar to that observed in deformation of copper by simple shear [23][24][25]. The variation in textures indicates differences in the modes of deformation in the indentation region, where a state of plane-strain compression is present directly underneath the indenter and a state of simple shear is present at the corners of the indenter.…”
Section: Nm Nmsupporting
confidence: 68%
“…These are typically referred to as α and β fibres, respectively, and have been observed following the deformation that occurs during rolling, which can be idealized as plane-strain compression. The deformation texture changes considerably in the highly strained region (III) in figure 8d, where the texture is similar to that observed in deformation of copper by simple shear [23][24][25]. The variation in textures indicates differences in the modes of deformation in the indentation region, where a state of plane-strain compression is present directly underneath the indenter and a state of simple shear is present at the corners of the indenter.…”
Section: Nm Nmsupporting
confidence: 68%
“…ECAP passes following BC route has not been observed [36], but it has been described in other studies [37,38] which used a die with a similar setting to the one in the present case. When the die has an external angle Ψ>0° the textures exhibit some predominant orientations with a continuous distribution along the orientation fibers with simple shear texture, where two symmetrical areas can be observed [37].…”
Section: Texture Analysismentioning
confidence: 45%
“…[1] While the effect of processing route on the microstructure and texture development in ECAE-deformed rods and bars has been investigated in a large number of publications [2][3][4][5][6] , only a few studies have been carried out for establishing this effect for ECAE-processed plates, for which new routes, different from those proposed for rod or bar samples, can be utilized. [7][8][9][10][11] In a recent work on AA1050 plates deformed by 8 ECAE passes either without rotation between passes (route A) or with 90 deg sequential rotations about the plate normal ND (route B C〈ND〉 ), [11] it was found that the microstructure obtained via route B C〈ND〉 was more refined than that obtained via route A.…”
mentioning
confidence: 99%
“…[11] The effect of the processing route on texture evolution in ECAE plates was investigated by Ferrasse et al [9,10] However, these authors considered a large number of orientation fibers differing from the shear-type fibers commonly adopted for characterizing ECAE textures, [2][3][4][5][6] which complicates a comparison of textures in their plate samples with those in rod samples described in many other publications. To better compare the general tendencies of texture evolution during ECAE of plates with those of rod samples, a modeling and experimental investigation of textures formed by ECAE has therefore been carried out and is described in the present work for commercial purity aluminum.…”
mentioning
confidence: 99%
See 1 more Smart Citation